Pulsed-wave Doppler Ultrasound in canine reproductive system – Part 2: use in the routine (Research, Society and Development, 2021)
Given the importance of the reproduction field combined with the use of the Pulsed-Wave (PW) ultrasound in the clinical routine, this study aims to review the application of this diagnostic method in the reproductive tract of females and males of the canine species. A narrative review was carried out by using scientific articles, monographs, dissertations and thesis published and available in online databases: Periodical Capes (Coordination for the Improvement of Higher Education Personnel), SciELO (Scientific Electronic Library Online) and Google Scholar, in addition to specific books on the topic. In female dogs, Doppler ultrasound can be used to evaluate hemodynamic conditions in the estrous cycle (e.g. estimating day of ovulation and fertility, diagnosing early pregnancy, abnormalities, and fetal stress, thus ensuring greater obstetric safety) and identification of diseases, thereby avoiding unnecessary surgical interventions. In male dogs, however, Doppler ultrasound is mainly used in vascular evaluations in order to identify hemodynamic changes due to occurrence of benign prostatic hyperplasia (BPH), most common disease of the prostate and in the assessment of testicular arteries to better understand spermatogenesis and diseases that affect the testicle. In this review, we demonstrate that the use of Doppler mode ultrasound, especially the PW, allows dynamic analysis in clinical examination and complements important information in the diagnosis and treatment of different reproductive disorders in dogs.